5-HT1A parital agonism and 5-HT7 antagonism restore episodic memory in subchronic phencyclidine-treated mice: role of brain glutamate, dopamine, acetylcholine and GABA. - Huang, Mei; Kwon, Sunoh; Rajagopal, Lakshmi; He, Wenqi; Meltzer, Herbert Y. (Psychopharmacology, 2018)
Rationale: The effect of atypical antipsychotic drugs (AAPDs), e.g., lurasidone, to improve cognitive impairment associated with schizophrenia (CIAS), has been suggested to be due, in part, to enhancing release of dopamine (DA), acetylcholine (ACh), and glutamate (Glu) in cortex and hippocampus.Results: The present study found acute lurasidone reversed the cognitive deficit in novel object recognition (NOR) in subchronic (sc) phencyclidine (PCP)-treated mice, an animal model for CIAS. This effect of lurasidone was blocked by pretreatment with the 5-HT1AR antagonist, WAY-100635, or the 5-HT7R agonist, AS 19. Lurasidone significantly increased medial prefrontal cortex (mPFC) ACh, DA, and Glu efflux, all of which were blocked by WAY-100635, with similar effects in the dorsal striatum (dSTR), except for the absence of an effect on Glu increase. AS 19 inhibited Glu, but not DA efflux, in the dSTR. The selective 5-HT7R antagonist, SB-26970, increased mPFC DA, 5-HT, Glu, and, importantly, also GABA efflux and striatal DA, NE, 5-HT, and Glu efflux, indicating tonic inhibition of the release of these neurotransmitters by 5-HT7R stimulation. These results provide new evidence that GABA release in the mPFC is tonically inhibited by 5-HT7R stimulation and suggest that a selective 5-HT7R antagonist might be clinically useful to enhance cortical GABAergic release. All SB-269970 effects were blocked by AS 19 or WAY-100635, suggesting 5-HT1AR agonism is necessary for the release of these neurotransmitters by SB-269970. Lurasidone increased ACh, DA, and NE but not Glu efflux in mPFC and dSTR DA and Glu efflux in 5-HT7 KO mice.Conclusion: We conclude that lurasidone-induced Glu efflux in mPFC requires 5-HT7R antagonism while its effects on cortical ACh and DA efflux are mainly due to 5-HT1AR stimulation.